Anesthetizing children: little people, big problems! - Lerman, Jerrold (Acta medica Lituanica, 2012)
At the time of graduation from residency, we possess the most knowledge of anesthesia than at any other time in our lives. Dr. S. Burwell, Dean of the Harvard Medical School, said in 1956: “Half of what you are taught as medical students will in 10 years have been shown to be wrong. And the trouble is none of your teachers know which half ”. Our understanding of the etiology and pathogenesis of many of the “big problems” that children present may lead to better outcomes and better quality of care, and it is the quintessential proposition for the delivery of excellence in clinical care to these “little people”. In this lecture we review a number of contentious and controversial issues that face pediatric anesthesiologists on a daily basis and present practical, evidence based approaches to addressing them.
Keywords: anesthetizing children; understanding of etiology and pathogenesis; excellence in clinical care